Preparation of low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber

By using high-strength, high-strength, high-strength, composite materials of graphene and natural rubber in rubber tires, the aging problem caused by compression fatigue and heat generation is solved, and the tire performance with low heat generation, high heat conductivity and long life is achieved.

CN118027527BActive Publication Date: 2025-03-11ZHONGBEI UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410109428.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-26
Publication Date
2025-03-11
Estimated Expiration
2044-01-26

AI Technical Summary

Technical Problem

During driving, existing rubber tires have increased compression fatigue due to stress deformation and heat conversion, which can accelerate tire aging and reduce service life.

Method used

The composite material of high-strength, high-tough ball mill-mercapto-coal modification of graphene and natural rubber is used to modify graphene oxide through ball mill to increase its edge carbon defects and surface radicals, and combine thiol modification to improve the interface interaction between graphene and rubber, forming a dual crosslinking network structure.

Benefits of technology

It effectively reduces the compression fatigue heat generation value of the tire, slows down the thermal aging speed, extends the service life of the tire, and improves the thermal conductivity and mechanical properties of the tire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118027527B_ABST
    Figure CN118027527B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of graphene and functional natural rubber composite materials, and in particular to the preparation of a low heat generation, high thermal conductivity and long life solid tire based on high-strength and high-toughness ball-milled thiol-synergistically modified graphene / natural rubber, wherein the graphene is modified by a ball-milled thiol-synergistic modification process, and then a high-strength and high-toughness ball-milled thiol-synergistically modified graphene / natural rubber is prepared by an aqueous phase synergistic coagulation process and a mechanical blending method, thereby obtaining a low heat generation, high thermal conductivity and long life solid tire. By ball-milling modification of graphene oxide slurry, its edge carbon defects are increased, and the free radical content on its surface is increased, while the edge carbon defects can increase the load during subsequent thiol modification, and the surface free radicals can remove the free radicals generated by the molecular chain breakage caused by heat and oxygen attack at the initial stage of tire dynamic driving heat generation, reduce the thermal decomposition of the natural rubber matrix molecular chain, reduce the fatigue compression heat generation value, and thus delay the aging speed of the tire.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphene and functional natural rubber composite materials, and in particular to the preparation of a low-heat-generating, high-thermal-conductivity, long-life solid tire based on high-strength and high-toughness ball-milling-thiol synergistically modified graphene / natural rubber. Background Art

[0002] Natural rubber (NR) has excellent properties such as high elasticity, high strength, high insulation, wear resistance and tear resistance. As a strategic resource, it plays an important role that cannot be replaced by artificial synthetic rubber. It is widely used in daily life and military defense fields, such as aircraft tires, engineering vehicle tires, and large defense truck tires.

[0003] However, NR has no use strength, and only reinforced NR can be used in various products. In addition, people have been studying the toughening of elastomers for a long time, and the main idea is to build a dissipative system in the elastic network. Based on this idea, many strategies have been developed in the reinforcement and toughening of NR, such as the introduction of nanocomposite structures, multiple crosslinking, copolymerization, metal coordination interactions, ionic interactions, and double network structures.

[0004] During driving, tires are affected by different stresses. While alternating external forces cause complex deformations, part of the energy is converted into heat energy due to the internal friction of the rubber, causing a large amount of heat to be generated inside the tire, which in turn causes a temperature rise. The increase in operating temperature will cause the molecular chains of the rubber matrix to break, generating a large number of free radicals, which will accelerate the aging of the rubber under the attack of heat and oxygen for a long time and shorten the service life of the molded tire. Therefore, it is very necessary to reduce the compression fatigue heat generation of rubber tires. Therefore, at present and in the future, tires are mainly developing in the direction of strengthening, reducing heat generation, and thus delaying aging, and developing in the direction of green and environmental protection.

[0005] The heat generated by rubber mainly comes from filler-filler friction, filler-rubber friction and rubber-rubber friction. At the same time, the unsaturated double bonds on the NR molecular chain break, generating active sites, which combine with oxygen free radicals to further cause the molecular chain to break and generate a large number of free radicals. Improving the dispersion of fillers in the matrix and improving the interaction between fillers and the matrix can reduce the dynamic friction between fillers and fillers and between fillers and the matrix. Therefore, removing free radicals and improving the interface interaction between fillers and the matrix are the key to giving rubber tires low heat generation performance.

[0006] Ball milling is a green and environmentally friendly method for modifying carbon materials. It mainly destroys some chemical bonds on the surface of carbon materials and makes them finer by the continuous collision and grinding of small balls moving at high speed. Ball milling modification can make carbon materials not only have a larger specific surface area and richer pore structure, but also have more oxygen-containing functional groups.

[0007] Graphene oxide has sp 2 The two-dimensional structure of the layer formed by the close stacking of hybrid carbon atoms has the advantages of high thermal conductivity, high strength, good thermal stability, and large specific surface area. The large number of oxygen-containing functional groups on the surface provide active sites for the modification of organic compounds. In addition, the special layered structure can increase edge defects for ball milling modification, increase the thiol grafting rate, and provide a basis for scavenging free radicals generated by thermal decomposition. Summary of the invention

[0008] In order to slow down the thermal aging speed of rubber tires and extend their service life, the present invention provides a method for preparing a low-heat-generating, high-thermal-conductivity, long-life solid tire based on high-strength and high-toughness ball milling-thiol synergistically modified graphene / natural rubber.

[0009] The present invention is achieved through the following technical scheme: preparation of a low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber, comprising the following steps:

[0010] (1) adding graphene oxide slurry into a ball mill, and ball milling for 15-120 min at a ball-to-material ratio of 100:0.5-2 and a rotation speed of 200-500 rpm to obtain a ball-milled modified graphene oxide slurry with increased carbon defects at the edge of the graphene oxide and increased surface free radical content;

[0011] (2) adding a mercapto-containing silane coupling agent to an alcohol aqueous solution, adjusting the pH after hydrolysis for a certain period of time, adding the ball-milled modified graphene oxide slurry obtained in step (1) under ultrasonic dispersion, heating the reaction for a certain period of time, and freeze-drying to obtain ball-milled-thiol synergistically modified graphene oxide;

[0012] (3) preparing a uniform aqueous dispersion of the ball-milled-thiol-synergistically modified graphene oxide obtained in step (2), and then adding the dispersion to natural rubber latex, stirring and mixing thoroughly to obtain a uniformly dispersed mixed emulsion, wherein the ball-milled-thiol-synergistically modified graphene oxide will form bound particles with the protein-phospholipid membrane positive ions on the surface of the rubber particles through electrostatic attraction and remain stable; adding a flocculant, since the repulsion between the particles that keeps the emulsion stable is reduced, flocculation occurs, and the rubber particles with the destroyed protective layer and the modified graphene oxide particles will further adsorb each other through the interaction force, and the bound particles and rubber particles will be orderly aggregated and synergistically precipitated in the aqueous phase; washing the obtained raw rubber with water, dehydrating, and drying to obtain the ball-milled-thiol-synergistically modified graphene / natural rubber masterbatch;

[0013] (4) placing the ball-milled-thiol synergistically modified graphene / natural rubber masterbatch prepared in step (3) in an internal mixer, mixing at a certain temperature, adding rubber additives and reinforcing fillers in sequence, discharging the rubber after uniform dispersion, and cooling to room temperature; then, mixing the rubber on an open mixer at a certain temperature, adding a vulcanizing agent, mixing evenly, and thinning the rubber until there are no bubbles in the rubber. After standing for a certain period of time, placing the rubber in a tire mold, and vulcanizing at a certain temperature and a certain pressure for a certain period of time, to obtain a low heat generation, high thermal conductivity, and long life solid tire based on high-strength and high-toughness ball-milled-thiol synergistically modified graphene / natural rubber.

[0014] As a further improvement of the technical solution of the present invention, in step (2), the volume ratio of alcohol to water in the alcohol aqueous solution is 5-9:1; the hydrolysis time of the mercapto-containing silane coupling agent in the alcohol aqueous solution is 1-5 hours, and the pH value after hydrolysis is adjusted to 7-13; the mercapto-containing silane coupling agent is selected from at least one of (3-mercaptopropyl)trimethoxysilane coupling agent, γ-mercaptopropyltriethoxysilane coupling agent and bis-[γ-(triethoxysilyl)propyl]tetrasulfide; the mass ratio of the mercapto-containing silane coupling agent to the graphene oxide in the ball-milled modified graphene oxide slurry is 1-4:1; the heating reaction temperature after adding the ball-milled modified graphene oxide slurry is 60-80°C, and the heating reaction time is 5-8 hours.

[0015] As a further improvement of the technical solution of the present invention, in step (3), the concentration of the prepared ball-milled-thiol synergistically modified graphene oxide uniform aqueous dispersion is 0.5-2wt%, and the mass ratio of the ball-milled-thiol synergistically modified graphene oxide to natural rubber is 0.25-1.5:100; and the flocculant is at least one of calcium chloride solution, sodium chloride solution, hydrochloric acid solution and formic acid solution.

[0016] As a further improvement of the technical solution of the present invention, in step (4), the added amounts of the raw materials are: 100 parts by mass of natural rubber in the natural rubber masterbatch modified by ball milling-thiol synergistically modified graphene, 30-90 parts by mass of reinforcing filler, and 10-20 parts by mass of rubber additives.

[0017] As a further improvement of the technical solution of the present invention, in step (4), the rubber additives include an antioxidant, an antioxidant, an activator, a softener and a vulcanization accelerator, and the mass ratio of the antioxidant, antioxidant, activator, softener, vulcanization accelerator to the vulcanizer is 2:2:5:2:2:2.

[0018] As a further improvement of the technical solution of the present invention, in step (4), the reinforcing filler is carbon black, selected from at least one of models N110, N330 and N660.

[0019] As a further improvement of the technical solution of the present invention, in step (4), the mixing temperature of the ball milling-thiol synergistically modified graphene / natural rubber masterbatch in the internal mixer is 105-120°C, and the mixing time is 12-20min; the mixing temperature in the open mixer is 50-70°C, and the mixing time is 8-12min.

[0020] As a further improvement of the technical solution of the present invention, in step (4), the storage time of the rubber mix is ​​18-36 hours; the vulcanization temperature is 135-170° C., the vulcanization pressure is 10-30 MPa, and the vulcanization time is 3-25 minutes.

[0021] The preparation of the low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber provided by the present invention has the following advantages compared with the prior art:

[0022] (1) Graphene is modified by ball milling-thiol synergistic modification process, and then the modified graphene reinforced and toughened natural rubber composite material is prepared by aqueous phase synergistic coagulation process and mechanical blending method, and then the low heat generation and high thermal conductivity tire is prepared. By ball milling modification of graphene oxide slurry, the carbon defects at its edge are increased, and the free radical content on its surface is increased. The edge carbon defects can increase the loading amount during subsequent thiol modification, and the surface free radicals can remove the free radicals generated by the molecular chain breakage caused by heat and oxygen attack at the initial stage of tire dynamic driving heat generation, reduce the thermal decomposition of NR matrix molecular chain, reduce fatigue compression heat generation value, and thus delay the aging rate of tire.

[0023] (2) The ball-milled modified graphene oxide is modified with thiol groups through a thiol-ene click chemistry reaction. On the one hand, the loading amount of the thiol-containing coupling agent can be increased. On the other hand, the thiol end group can react with the rubber to form a single sulfur bond, which can not only reduce the time required for the vulcanization of natural rubber and improve the processing performance; but also improve the interfacial interaction between the ball-milled-thiol synergistically modified graphene and the natural rubber matrix. The double network formed with the rubber vulcanization cross-linking network improves the mechanical and thermal conductivity of the final prepared rubber tire, reduces the frictional heat generated between the filler-matrix and the filler-filler, thereby slowing down the thermal aging rate of the rubber tire during dynamic driving and extending the service life of the tire. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 Infrared spectra of ball-milled-thiol synergistically modified graphene oxide (BGO-SH) prepared in Example 1 and GO in Comparative Example 1.

[0027] Figure 2 This is the full XPS spectrum of BGO-SH prepared in Example 1 and GO in Comparative Example 1.

[0028] Figure 3 XPS spectra of C1s, Si 2p and S2p of BGO-SH prepared in Example 1.

[0029] Figure 4 TG weight loss curves of BGO-SH prepared in Example 1 and GO prepared in Comparative Example 1.

[0030] Figure 5 SEM photos of GO (a), BGO-SH prepared in Example 1 (b), and a low heat generation, high thermal conductivity, and long life solid tire material based on high-strength and high-toughness ball milling-thiol synergistically modified graphene / natural rubber (c).

[0031] Figure 6 This is the EDX energy spectrum of C, S and Si of BGO-SH prepared in Example 1.

[0032] The test method of the above-mentioned figure is:

[0033] Infrared spectrum: The IS50 Fourier transform infrared spectrometer from Thermo Fisher Scientific was used to analyze the functional groups of the materials. The test range was 500-4000cm -1 , grind the material sample and KBr powder at a ratio of 1:100, mix well and press into tablets.

[0034] XPS spectrum: The test and analysis were performed using the NEXSA X-ray photoelectron spectrometer from Thermo Fisher Scientific, USA. The scanning mode was CAE mode, the pass energy for full spectrum scanning was 160 eV, and the pass energy for narrow spectrum scanning was 40 eV.

[0035] TG weight loss curve: The weight loss test was carried out using a Q50 thermogravimetric analyzer from TA Company of the United States. The test was carried out from room temperature to 800°C at a heating rate of 10°C / min in a N2 atmosphere.

[0036] SEM photos: The particles and brittle fracture surfaces of Example 1 and Comparative Example 1 were tested using a SU8010 scanning electron microscope produced by Hitachi, Japan, at a voltage of 10 KV.

[0037] Depend on Figure 1 It can be seen that for GO, the characteristic peak of carbonyl (-C=O) appears at 1728cm -1 3442cm -1 、1628cm -1 and 1401cm -1 The peaks at 1236 cm-1 and 1277 cm-2 correspond to hydroxyl (-OH), -C=C and carboxyl (-COOH) respectively. For BGO-SH, in addition to the above characteristic peaks, two new characteristic peaks appear, namely 1236 cm-1 and 1277 cm-2. -1 Si-C and 1114cm -1 The Si-O stretching vibration peak at , indicating that KH580 has been successfully grafted onto the surface of ball-milled modified GO (BGO).

[0038] Depend on Figure 2 It can be seen that the peaks of S2p and Si 2p appear in the full spectrum of BGO-SH, indicating the presence of KH580 on the BGO surface. At the same time, the O content decreases from 31.04% to 22.26%, proving that the silanol in KH580 reacts with the -OH on the GO surface and is grafted onto the BGO surface through dehydration condensation. Figure 3 As shown, further analysis of its Si 2p, C 1s and S2p deconvolution images shows the presence of obvious Si-O-Si (102.78 eV), CS (164.24 eV) and -SH (163 eV) bonds, indicating that KH580 was successfully grafted on the BGO surface.

[0039] Depend on Figure 4 It can be seen that the thermal weight loss around 100°C is mainly due to the volatilization of water. 150-250°C is mainly due to the thermal decomposition of unstable oxygen functional groups of graphene oxide. In contrast, from room temperature to 800°C, the thermal weight loss of BGO-SH is 50.32wt%. The significant decrease in the total weight loss indicates that silicon-containing functional groups such as Si-O-Si are grafted on the surface of graphene oxide because they have higher thermal stability than CC and CO. In addition, a new thermal degradation stage appeared in the BGO-SH spectrum at 300-400°C, with a weight loss of 14.54wt%, indicating that the thiol group has decomposed, further proving that KH580 is grafted on the BGO surface.

[0040] Depend on Figure 5 It can be seen that for the original GO ( Figure 5 a), its surface has a typical wrinkled lamellar structure, and the flake diameter is relatively large. After ball milling, BGO ( Figure 5b) The morphology of the sheet changes significantly, the sheet is destroyed by the mechanical force of ball milling, more edge structures appear, and the sheet diameter decreases. For the brittle fracture surface of BGO-SH modified NR vulcanizate (NR / BGO-SH / CB), the composite particles are well dispersed in the rubber matrix, and no obvious agglomerates appear.

[0041] Depend on Figure 6 It can be seen that after thiol modification, the surface of BGO-SH contains S and Si elements, which further proves that KH580 is successfully grafted onto the BGO surface. DETAILED DESCRIPTION

[0042] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0043] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0044] The present invention provides a specific embodiment of the preparation of a low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber, comprising the following steps:

[0045] (1) adding graphene oxide slurry into a ball mill, and ball milling for 15-120 min at a ball-to-material ratio of 100:0.5-2 and a rotation speed of 200-500 rpm; obtaining a ball-milled modified graphene oxide slurry with increased graphene oxide edge carbon defects and surface free radical content; the edge carbon defects can increase the loading amount during subsequent thiol modification, and the surface free radicals can remove free radicals generated by the breakage of natural rubber molecular chains caused by heat and oxygen attack;

[0046] (2) adding a mercapto-containing silane coupling agent to an alcohol aqueous solution, adjusting the pH after hydrolysis for a certain period of time, adding the ball-milled modified graphene oxide slurry obtained in step (1) under ultrasonic dispersion, heating the reaction for a certain period of time, and freeze-drying to obtain ball-milled-thiol synergistically modified graphene oxide;

[0047] (3) preparing a uniform aqueous dispersion of the ball-milled-thiol-synergistically modified graphene oxide obtained in step (2), and then adding the dispersion to natural rubber latex, stirring and mixing thoroughly to obtain a uniformly dispersed mixed emulsion, wherein the ball-milled-thiol-synergistically modified graphene oxide will form bound particles with the protein-phospholipid membrane positive ions on the surface of the rubber particles through electrostatic attraction and remain stable; adding a flocculant, since the repulsion between the particles that keeps the emulsion stable is reduced, flocculation occurs, and the rubber particles with the destroyed protective layer and the modified graphene oxide particles will further adsorb each other through the interaction force, and the bound particles and rubber particles will be orderly aggregated and synergistically precipitated in the aqueous phase; washing the obtained raw rubber with water, dehydrating, and drying to obtain the ball-milled-thiol-synergistically modified graphene / natural rubber masterbatch;

[0048] (4) placing the ball-milled-thiol synergistically modified graphene / natural rubber masterbatch prepared in step (3) in an internal mixer, mixing at a certain temperature, adding rubber additives and reinforcing fillers in sequence, discharging the rubber after uniform dispersion, and cooling to room temperature; then mixing the rubber on an open mixer at a certain temperature, adding a vulcanizing agent, mixing evenly, and thinning the rubber until there are no bubbles in the rubber. After standing for a certain period of time, placing the rubber in a tire mold, and vulcanizing at a certain temperature and a certain pressure for a certain period of time to obtain a natural rubber tire with low heat generation and high thermal conductivity that is reinforced and toughened by ball-milled-thiol synergistically modified graphene.

[0049] Taking the mercapto-containing silane coupling agent, γ-mercaptopropyltriethoxysilane coupling agent (KH580), as an example, the mechanism of preparing ball milling-mercapto-synergistic modified graphene oxide and the mechanism of forming a double cross-linked network structure in the natural rubber composite material are explained:

[0050] During the ball milling process, the GO sheets are broken and reorganized under the action of mechanical force, their size gradually decreases, and a large number of irregular broken edge structures are formed; at the same time, the SP 2 The ordered lattice is destroyed and free radicals are formed. Defects, edges and free radicals increase with the increase of ball milling time:

[0051]

[0052] During the hydrolysis process, the silicon-oxygen bond (Si-O) in the KH580 molecular chain breaks under the action of water to form silanol (Si-OH):

[0053]

[0054] The formed silanol undergoes a dehydration condensation reaction with the oxygen-containing functional groups (such as hydroxyl groups) on the surface of BGO and is grafted onto the surface of BGO by forming chemical bonds:

[0055]

[0056] Mechanism of formation of double cross-linked network structure in natural rubber composites:

[0057]

[0058] During the NR vulcanization process, on the one hand, NR reacts with the vulcanizing agent to form a vulcanized cross-linked network structure; on the other hand, the ethoxy groups in KH580 are thermally decomposed to generate highly active silanols, which construct a chemically bonded BGO-S-NR cross-linked network between the GO and NR molecular chains through the thiol (-SH) group, forming a unique double cross-linked network structure. This not only shortens the time required for natural rubber vulcanization and improves processing performance, but also improves the interfacial interaction between ball milling-thiol synergistically modified graphene and the natural rubber matrix. The constructed double network structure improves the mechanical and thermal conductivity of the final rubber tire, reduces the frictional heat between the filler-matrix and filler-filler, and the free radicals on the graphene surface given by the ball milling modification can remove the free radicals generated by the molecular chain breakage caused by heat and oxygen attack during the dynamic driving of the tire, thereby reducing the thermal decomposition of the natural rubber matrix molecular chain, slowing down the thermal aging rate of the rubber tire during dynamic driving, and extending the service life of the rubber tire.

[0059] In one embodiment provided by the present invention, in step (2), the volume ratio of alcohol to water in the alcohol aqueous solution is 5-9:1; the hydrolysis time of the mercapto-containing silane coupling agent in the alcohol aqueous solution is 1-5 hours, and the pH value after hydrolysis is adjusted to 7-13; the mercapto-containing silane coupling agent is selected from at least one of (3-mercaptopropyl)trimethoxysilane coupling agent, γ-mercaptopropyltriethoxysilane coupling agent and bis-[γ-(triethoxysilyl)propyl]tetrasulfide; the mass ratio of the mercapto-containing silane coupling agent to the graphene oxide in the ball-milled modified graphene oxide slurry is 1-4:1; the heating reaction temperature after adding the ball-milled modified graphene oxide slurry is 60-80°C, and the heating reaction time is 5-8 hours.

[0060] In another embodiment provided by the present invention, in step (3), the concentration of the prepared ball-milled-thiol synergistically modified graphene oxide uniform aqueous dispersion is 0.5-2wt%, and the mass ratio of the ball-milled-thiol synergistically modified graphene oxide to natural rubber is 0.25-1.5:100; and the flocculant is at least one of calcium chloride solution, sodium chloride solution, hydrochloric acid solution and formic acid solution.

[0061] In one embodiment provided by the present invention, in step (4), the added amounts of the raw materials are: 100 parts by mass of natural rubber in the natural rubber masterbatch modified by ball milling-thiol synergistically modified graphene, 30-90 parts by mass of reinforcing filler, and 10-20 parts by mass of rubber additives.

[0062] In another embodiment provided by the present invention, in step (4), the rubber additives include an antioxidant, an antioxidant, an activator, a softener and a vulcanization accelerator, and the mass ratio of the antioxidant to the antioxidant, the activator, the softener, the vulcanization accelerator and the vulcanizing agent is 2:2:5:2:2:2.

[0063] In one embodiment provided by the present invention, in step (4), the reinforcing filler is carbon black, selected from at least one of models N110, N330 and N660.

[0064] In another embodiment provided by the present invention, in step (4), the mixing temperature of the ball milling-thiol synergistically modified graphene / natural rubber masterbatch in the internal mixer is 105-120°C, and the mixing time is 12-20min; the mixing temperature in the open mixer is 50-70°C, and the mixing time is 8-12min.

[0065] In one embodiment provided by the present invention, in step (4), the storage time of the rubber mix is ​​18-36 hours; the vulcanization temperature is 135-170° C., the vulcanization pressure is 10-30 MPa, and the vulcanization time is 3-25 minutes.

[0066] The specific embodiments of the present invention are described in detail below.

[0067] Example 1

[0068] A preparation method of a low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber, comprising the following steps:

[0069] (1) adding graphene oxide slurry to a planetary ball mill, and ball milling for 60 min at a ball-to-material ratio of 100:1.5 and a rotation speed of 500 rpm; obtaining a ball-milled modified graphene oxide slurry with improved carbon defects at the edge of graphene oxide and surface free radical content; (2) adding γ-mercaptopropyltriethoxysilane coupling agent to an alcohol-water solution with a volume ratio of 9:1, hydrolyzing for 2 h, adjusting the pH to 7, and adding the coupling agent to the graphene oxide in the ball-milled modified graphene oxide slurry at a mass ratio of 2.5:1 under an ultrasonic power of 200 W; 1) the obtained ball-milled modified graphene oxide slurry is reacted at 70° C. for 8 h, and then freeze-dried to obtain ball-milled-thiol synergistically modified graphene oxide; (3) a uniform aqueous dispersion of the ball-milled-thiol synergistically modified graphene oxide obtained in step (2) is prepared with a concentration of 1 wt %, and then the dispersion is added to natural rubber latex at a mass ratio of modified graphene oxide to natural rubber of 0.5:100, and after sufficient stirring and mixing, a uniformly dispersed mixed emulsion is obtained, wherein the ball-milled-thiol synergistically modified graphene oxide will be combined with the protein on the surface of the rubber particles. The positive ions of the phospholipid membrane form bound particles through electrostatic attraction and remain stable; adding a flocculant calcium chloride solution, the repulsion between the particles that keeps the emulsion stable is reduced, so flocculation occurs, and the rubber particles with the damaged protective layer and the modified graphene oxide particles will further adsorb each other through the interaction force, and the bound particles and rubber particles will be orderly aggregated and precipitated in the water phase; the obtained raw rubber is washed with water, dehydrated, and dried until the moisture content is less than 1% as measured by an infrared moisture meter, to obtain a ball-milled-thiol-synergistically modified graphene / natural rubber masterbatch; (4) adding 100 The ball-milled-thiol-synergistically modified graphene / natural rubber masterbatch prepared in step (3) of 100 g natural rubber was placed in an internal mixer and mixed for 4 min at 110 ° C and 40 rpm. Then, 2 g of antioxidant 2,2,4-trimethyl-1,2-dihydroquinoline polymer, 2 g of antioxidant N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, and 2 g of vulcanization accelerator N-(oxydiethylene)-2-benzothiazolesulfonamide were added and mixed for 4 min. 5 g of activator ZnO, 2 g of softener stearic acid (SA) and 30 g of N330 carbon black was added and the mixing was continued for 4 minutes; then 30g N330 carbon black was added and the mixing was continued for 4 minutes, the rubber was discharged and cooled to room temperature; then the rubber was mixed on an open mill at 60°C, 2g sulfur was added, and the rubber was mixed for 8 minutes to be evenly mixed, and then the rubber was thinly passed until there were no bubbles in the rubber. After standing for 24 hours, the rubber was placed in a tire mold, and the vulcanization temperature was 150°C, the vulcanization pressure was 15MPa, and the vulcanization time was 9min (Tc90), to obtain a ball-milled-thiol-synergistically modified graphene reinforced and toughened natural rubber tire with low heat generation and high thermal conductivity, wherein t c90 Measured by Rubber Process Analyzer (RPA).

[0070] Example 2

[0071] A preparation method of a low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber, comprising the following steps:

[0072] (1) Same as (1) of Example 1;

[0073] (2) adding γ-mercaptopropyltriethoxysilane coupling agent to an alcohol-water solution with a volume ratio of 9:1, hydrolyzing for 2 hours, adjusting the pH to 7, adding the ball-milled modified graphene oxide slurry obtained in step (1) at an ultrasonic power of 200 W according to a mass ratio of coupling agent to graphene oxide in the ball-milled modified graphene oxide slurry of 2:1, reacting at 70° C. for 8 hours, and freeze-drying to obtain ball-milled-thiol synergistically modified graphene oxide;

[0074] (3) Same as (3) of Example 1;

[0075] (4) Same as (4) of Example 1.

[0076] Comparative Example 1

[0077] A method for preparing a graphene oxide-natural rubber tire comprises the following steps:

[0078] ① The same as (3) of Example 1, except that the ball-milled-thiol-synergistically modified graphene in Example 1 is replaced with graphene oxide;

[0079] ②Same as (4) of Example 1.

[0080] Comparative Example 2

[0081] A method for preparing a ball-milled modified graphene oxide-natural rubber tire comprises the following steps:

[0082] ①Same as (1) of Example 1;

[0083] ② The same as (3) of Example 1, except that the ball-milled-thiol-synergistically modified graphene in Example 1 is replaced by the ball-milled modified graphene oxide in (1);

[0084] ③Same as (4) of Example 1.

[0085] Comparative Example 3

[0086] A method for preparing a mercapto-modified graphene oxide-natural rubber tire comprises the following steps:

[0087] ① The same as (2) of Example 1, except that the ball-milled modified graphene oxide slurry is replaced with graphene oxide;

[0088] ② The same as (3) of Example 1, except that the ball-milled-thiol-synergistically modified graphene in Example 1 is replaced with thiol-modified graphene;

[0089] ③Same as (4) of Example 1.

[0090] The properties of the modified NR composite materials were sampled from the tires prepared in Examples 1 to 2 and Comparative Examples 1 to 3 and tested. The tensile properties were tested according to ISO 37-2005 and the tensile rate was 500 mm / min. The tear properties were tested according to GB / T529-2008. The compression fatigue heat generation properties were tested according to GB / T 1687.1-2016. The thermal conductivity properties were tested according to GB / T 11205-2009.

[0091] Table 1 Properties of prepared tire rubber composites

[0092] sample Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength(MPa) 29.12 27.53 25.12 28.54 27.33 Tear strength(N / mm) 105.45 97.45 81.34 92.91 86.32 Compression fatigue heat generation (℃) 16.62 18.35 22.59 18.35 17.94 <![CDATA[Thermal conductivity (Wm -1 K -1 )]]> 0.3959 0.3713 0.2921 0.3265 0.3516

[0093] It can be seen from Table 1 that the tire rubber composite material prepared by the present invention has the characteristics of high thermal conductivity, low compression heat generation and excellent mechanical properties.

[0094] The above is only a specific implementation of the present invention, which enables those skilled in the art to understand or implement the present invention. Although detailed descriptions are given with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments, and they should all be covered by the protection scope of the claims.

Claims

1. Preparation of low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber, characterized in that: The following steps are involved: (1) adding graphene oxide slurry into a ball mill, and ball milling for 15-120 min at a ball-to-material ratio of 100:0.5-2 and a rotation speed of 200-500 rpm; obtaining a ball-milled modified graphene oxide slurry with increased carbon defects at the edge of graphene oxide and increased surface free radical content; (2) adding a mercapto-containing silane coupling agent to an alcohol-water solution, adjusting the pH after hydrolysis, adding the ball-milled modified graphene oxide slurry obtained in step (1) under ultrasonic dispersion, heating for reaction, and freeze-drying to obtain ball-milled-thiol-synergistically modified graphene oxide; the volume ratio of alcohol to water in the alcohol-water solution is 5-9:1; the mass ratio of the mercapto-containing silane coupling agent to the graphene oxide in the ball-milled modified graphene oxide slurry is 1-4:1; (3) preparing a uniform aqueous dispersion of the ball-milled-thiol-synergistically modified graphene oxide obtained in step (2), and then adding it to natural rubber latex, stirring and mixing thoroughly to obtain a uniformly dispersed mixed emulsion, wherein the ball-milled-thiol-synergistically modified graphene oxide will form bound particles with the protein-phospholipid membrane positive ions on the surface of the rubber particles through electrostatic attraction and remain stable; adding a flocculant, because the repulsion between the particles that keeps the emulsion stable is reduced, flocculation occurs, and the rubber particles with the destroyed protective layer and the modified graphene oxide particles will adsorb each other through the interaction force, and the bound particles and rubber particles will be orderly aggregated and precipitated in the aqueous phase; washing the obtained raw rubber with water, dehydrating, and drying to obtain a ball-milled-thiol-synergistically modified graphene / natural rubber masterbatch; the concentration of the prepared ball-milled-thiol-synergistically modified graphene oxide uniform aqueous dispersion is 0.5-2wt%, and the mass ratio of the ball-milled-thiol-synergistically modified graphene oxide to natural rubber is 0.25-1.5:100; (4) The ball-milled-thiol-synergistically modified graphene / natural rubber masterbatch prepared in step (3) is placed in an internal mixer, and mixed at a temperature of 105-120°C. Rubber additives and reinforcing fillers are added in sequence, and the rubber material is discharged after being evenly dispersed, and cooled to room temperature; then the rubber material is open-mixed at a temperature of 50-70°C on an open mixer, and a vulcanizing agent is added. After mixing evenly, the rubber material is thinly passed until there are no bubbles in the rubber material. After standing, the rubber material is placed in a tire mold, and vulcanized at a temperature of 135-170°C and a pressure of 10-30 MPa to obtain a low heat generation, high thermal conductivity, and long life solid tire based on high strength and high toughness ball-milled-thiol-synergistically modified graphene / natural rubber.

2. The preparation of a low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber according to claim 1, characterized in that: In step (2), the hydrolysis time of the mercapto-containing silane coupling agent in the alcohol aqueous solution is 1-5 h, and the pH value after hydrolysis is adjusted to 7-13; the mercapto-containing silane coupling agent is selected from at least one of (3-mercaptopropyl)trimethoxysilane coupling agent, γ-mercaptopropyltriethoxysilane coupling agent and bis-[γ-(triethoxysilyl)propyl]tetrasulfide; the heating reaction temperature after adding the ball-milled modified graphene oxide slurry is 60-80°C, and the heating reaction time is 5-8 h.

3. The preparation of a low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber according to claim 1, characterized in that: In step (3), the flocculant is at least one of a calcium chloride solution, a sodium chloride solution, a hydrochloric acid solution and a formic acid solution.

4. The preparation of a low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber according to claim 1, characterized in that: In step (4), the addition amounts of the raw materials are: 100 parts by weight of natural rubber in the natural rubber masterbatch modified by ball milling-thiol synergistically modified graphene, 30-90 parts by weight of reinforcing filler, and 10-20 parts by weight of rubber additives.

5. The preparation of a low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber according to claim 1, characterized in that: In step (4), the rubber additives include an antioxidant, an antioxidant, an activator, a softener and a vulcanization accelerator, and the mass ratio of the antioxidant, antioxidant, activator, softener, vulcanization accelerator to the vulcanizer is 2:2:5:2:2:

2.

6. The preparation of a low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber according to claim 1, characterized in that: In step (4), the reinforcing filler is carbon black, selected from at least one of models N110, N330 and N660.

7. The preparation of a low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber according to claim 1, characterized in that: In step (4), the mixing time of the ball-milled-thiol synergistically modified graphene / natural rubber masterbatch in the internal mixer is 12-20 min; and the mixing time in the open mixer is 8-12 min.

8. The preparation of a low heat generation, high thermal conductivity and long life solid tire based on high strength and high toughness ball milling-thiol synergistic modified graphene / natural rubber according to claim 1, characterized in that: In step (4), the storage time of the rubber mixture is 18-36 h; and the vulcanization time is 3-25 min.

Citation Information

Patent Citations

  • Graphene-containing insulated radiating composition and preparation and application thereof

    CN103804942A

  • Preparation of long-service-life load-bearing tire with graphene / different-particle-size carbon black synergistic vulcanization modified natural rubber

    CN116855000A